Role of a Learning Management System in Medical Curriculum; Students’ initial perception about the use of LMS-Moodle at Fazaia Ruth Pfau Medical College: Role of a Learning Management System in Medical Curriculum - Faisal Rahim, Muhammad; Ahmed Skaikh, Masood; Ul Haque, Sama; Jabeen, Shah; Ansari, Tahir (Pakistan Journal of Health Sciences, 2022)
The modern medical curriculum has to deliver a great amount of educational content and knowledge to the learners as changes in content delivery are occurring at a very high speed. New technology and tools are introduced each day for this purpose. MS Moodle helps in students` learning mainly through tools which provides students` interactions like discussions forums, timed assignments, and use of computer-based testing as E-assessment tools. During implementation of e-learning platform LMS-Moodle, it was felt necessary to examine students’ perception about Moodle. Objectives: To assess students initial perception of about the use of the learning management system Moodle in integrated modular systems at FRPMC. Methods: The study design was cross-sectional and observational in nature with a quantitative data collection method. The study was conducted at Fazaia Ruth Pfau Medical College, Karachi during 2021 to 2022. Total number of participants was 100. The instrument used in the research was a questionnaire consisted of 17 statements presented with 1-5-point Likert scale for responses. The Cronbach alpha test was employed for reliability test. The analysis was done by SPSS version 23. Results: By analyzing overall received feedbacks of participants, the cumulative mean on 5-point Likert scale was 3.3 where 1 considered as strongly disagree and 5 as strongly agree. Conclusions: It was concluded that majority of participants studying in Fazaia Ruth Pfau Medical College have positive perception and experience of using Learning Management System Moodle in medical curriculum.